Pemanfaatan Reaktor Kontinu dan Katalis Zeolit dalam Konversi Termal Limbah Poliolefin menjadi Bahan Bakar Ramah Lingkungan - Masri Ali; Masri Ibrahim; M. Nizar Machmud (Design Journal, 2025)
This study investigated the conversion of plastic waste into fuel oil through thermal and catalytic cracking with an innovative reactor. The study analyzed the effect of plastic type (LDPE, HDPE, PP), reactor temperature (400-550°C), and catalyst type (HZSM-5, ZSM-5, Ni-Mo/Zeolite) on the yield and characteristics of liquid products. The experimental results showed that LDPE produced the highest liquid product (78.5%), the optimum temperature was 500°C, and the HZSM-5 catalyst gave the best performance. GC-MS analysis identified the main components of C5-C12 hydrocarbons according to the characteristics of fuel oil. The liquid product had a calorific value of 42.5 MJ/kg and a sulfur content of <10 ppm with an energy efficiency of 65%. The results of the study prove the effectiveness of the innovative reactor in overcoming the problem of plastic waste while producing alternative energy